Detection of the long noncoding RNAs nuclear‐enriched autosomal transcript 1 (NEAT1) and metastasis associated lung adenocarcinoma transcript 1 in the peripheral blood of HIV‐1‐infected patients. Issue 1 (2nd July 2015) - Jin, C; Peng, X; Xie, T; Lu, X; Liu, F; Wu, H; Yang, Z; Wang, J; Cheng, L; Wu, N
Abstract : Objectives: Long noncoding RNAs (lncRNAs) in HIV‐1 infection have not been extensively studied. Here we detected two lncRNAs, nuclear‐enriched autosomal transcript 1 (NEAT1) and metastasis associated lung adenocarcinoma transcript 1 (MALAT1), in peripheral blood mononuclear cells (PBMCs) and plasma of HIV‐1‐infected patients. Methods: Fifty‐nine HIV‐1‐infected patients and 21 healthy controls were recruited for the study, of whom 31 patients were highly active antiretroviral therapy (HAART)‐naïve and 28 patients had been receiving HAART for more than 1 year with undetectable viral loads. Total RNA was extracted from PBMCs and plasma, and levels of NEAT1 and MALAT1 were determined by quantitative real‐time polymerase chain reaction. Results: We found that the levels of NEAT1 and MALAT1 in PBMCs were up‐regulated in HAART‐naïve patients and were reduced in patients receiving HAART. NEAT1 was down‐regulated in the plasma of infected patients and expression was correlated with CD4 T‐cell count. Conclusions: Our findings suggest that NEAT1 and MALAT1 may interact with HIV‐1 in vivo and that the presence of NEAT1 in plasma is a potential biomarker of HIV‐1 infection.